Construction method of double-anode-layer low-contact-resistance PEM electrolyzed water membrane electrode

By adopting a dual anode layer structure and a titanium felt gas diffusion layer without precious metal coating in the PEM electrolytic water film electrode, the problem of large contact impedance between the anode layer and the gas diffusion layer is solved, and efficient electrolytic water decomposition and cost reduction effect is achieved.

CN119663317APending Publication Date: 2025-03-21GUANGDONG TAIJI POWER CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411856836.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the existing PEM electrolytic film electrodes, there is a large contact impedance between the anode layer IrOx and TiO2 on the surface of the gas diffusion layer, resulting in large voltage loss, low hydrogen production efficiency, and the precious metal plating process is complex and costly.

Method used

A double anode layer structure is adopted, and an anode catalytic layer with a double-layer structure is formed by spraying the first anode ink and the second anode ink, and a titanium felt without precious metal coating is used as the anode gas diffusion layer to avoid direct contact between IrOx and TiO2 and reduce contact impedance.

Benefits of technology

The contact impedance between the anode layer and the gas diffusion layer is significantly reduced, the film electrode performance is improved, the amount of precious metals and the process cost are reduced, and the performance is close to or better than that of the film electrodes using precious metal coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663317A_ABST
    Figure CN119663317A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of new energy, and discloses a construction method of a double-anode-layer low-contact-impedance PEM electrolytic water membrane electrode. Wherein the double-anode layer consists of an anode coating A with excellent catalytic performance and an anode coating B with excellent conductivity. And the anode coating B with excellent conductivity is added, so that the contact resistance between the anode layer and an anode gas diffusion layer without a noble metal coating can be effectively reduced. Compared with an existing technology using a gas diffusion layer with a precious metal coating, the PEM electrolyzed water membrane electrode prepared by using the gas diffusion layer without the precious metal coating has the advantages that the performance is close to or even better than that of the PEM electrolyzed water membrane electrode prepared by using the gas diffusion layer without the precious metal coating. Meanwhile, the gas diffusion layer without a plating layer is used in the method, so that the use amount of precious metal and the cost caused by a complex plating layer process can be greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new energy, and specifically relates to a method for constructing a double-anode layer low-contact impedance PEM water electrolysis membrane electrode. Background Art

[0002] As the energy demand of various countries increases, the use of renewable energy such as wind and solar energy is growing rapidly around the world. Electrolyzer is a device that can use renewable energy to electrolyze water to produce hydrogen, and the produced hydrogen can be used as fuel in fuel cells to generate electricity. Therefore, hydrogen is regarded as a green carrier that can store renewable energy for a long time. Among many electrolyzers, PEM electrolyzer has attracted attention from various countries due to its high efficiency, large energy capacity and flexible matching of renewable energy. However, the high production cost of PEM electrolyzer limits its large-scale commercial application.

[0003] The PEM water electrolysis membrane electrode is the core component of the PEM electrolyzer and is also the key to determining the cost of the PEM electrolyzer. The PEM water electrolysis membrane electrode is composed of a catalyst, a proton membrane, and a gas diffusion layer. Among them, the anode catalyst is generally an Ir or Ru-based catalyst, the cathode catalyst is generally a Pt-based catalyst, the anode gas diffusion layer is a titanium felt or sintered titanium plate material, and the cathode gas diffusion layer is a carbon paper material. The conventional manufacturing process of the PEM water electrolysis membrane electrode is: first, the anode catalyst and the cathode catalyst are mixed with ionomers, solvents, etc. to form a catalyst ink. Then, the anode catalyst and cathode catalyst ink are sprayed on both sides of the proton exchange membrane respectively to form a three-in-one "sandwich" structure. Finally, the anode and cathode gas diffusion layers are compressed and assembled with the three-in-one structure to form a five-in-one structure of "cathode gas diffusion layer-cathode catalyst layer-proton exchange membrane-anode catalyst layer-anode gas diffusion layer".

[0004] The anode catalyst materials of the classic PEM water electrolysis membrane electrode are Ir-based and Ru-based catalysts. Based on the comprehensive consideration of catalytic performance and durability, IrOx is the most common choice in the industry, because Ru-based catalysts and other chemical forms of Ir-based catalysts have poor stability. Studies have shown that there is a large contact impedance between metal oxide catalysts such as IrOx and the TiO2 layer on the surface of titanium felt, which will cause the PEM water electrolysis membrane electrode to have a greater voltage loss during operation, greatly reducing the efficiency of hydrogen production by electrolysis of water. A classic strategy to reduce voltage loss is to form a precious metal coating on the surface of titanium felt to avoid or slow down the formation of the TiO2 layer on the surface of titanium felt to reduce contact impedance. Unfortunately, the process of forming a precious metal coating on the surface of titanium felt is complicated, and the amount of precious metal used is relatively large (>1 mg / cm 2 ), resulting in a sharp increase in its cost to 2 to 3 times that of the substrate without precious metal coating.

[0005] In this regard, people have developed a variety of technologies, which can be mainly divided into two categories. One is to reduce the contact impedance between the anode coating and the titanium felt without precious metal coating. The other is to improve the coating process of titanium felt and reduce the amount of precious metals. For example, CN114808000A discloses a method for constructing an efficient and stable PEM electrolysis anode catalyst layer, constructing a multilayer anode coating, adjusting the catalyst, ionomer and PTFE ratio of the anode layer close to the gas diffusion layer side to optimize its electronic conduction with the gas diffusion layer. CN116905002A discloses a method for preparing a low interface impedance PEM electrolysis water membrane electrode anode catalyst layer. By coating the anode catalyst on the surface of the titanium felt and the surface of the proton exchange membrane respectively, the bonding force between the catalyst layer and the titanium felt is enhanced, the contact area between the two-phase interface is increased, and the interface contact impedance between the electrolysis water membrane electrode collector diffusion layer and the catalyst layer is effectively improved, the membrane electrode performance is improved, and it is conducive to the construction of a low precious metal loading membrane electrode. The above technology can optimize the contact surface microstructure between the anode layer and the gas diffusion layer to a certain extent, but it cannot solve the problem of large contact impedance between IrOx and TiO2 materials. CN118756205A discloses a method for preparing a titanium fiber felt composite material, comprising the following steps: subjecting the titanium fiber felt to acidification treatment to obtain an acidified titanium fiber felt; placing the acidified titanium fiber felt in an electroplating solution for electroplating to obtain a titanium fiber felt loaded with a platinum layer; sintering the titanium fiber felt loaded with a platinum layer to obtain the titanium fiber felt composite material. CN115216798A discloses a method for preparing an anode gas diffusion layer, which uses photochemical plating to quickly prepare a precious metal coating on the surface of a titanium substrate. The precious metal coating is thin, the precious metal nanoparticles in the coating have good dispersion, the coating structure is dense, and the amount of precious metal is low. At the same time, the precious metal coating inhibits the oxidation of the surface of the titanium substrate, effectively improving the conductivity of the anode gas diffusion layer. CN117051424A discloses a gas diffusion layer with a porous structure and an oxide coating is arranged on a metal substrate by adopting a PVD physical vapor deposition method. The coating on the metal substrate is more uniform, especially suitable for a metal substrate with a porous structure. A uniform coating deposition can be obtained on the positive and negative planes of the substrate and on the side of the fiber filament, with low contact resistance, high corrosion resistance, and high anode reaction catalytic ability; at the same time, the coating and the metal substrate have good bonding strength, and the coating bonding strength is better than other film-forming methods such as evaporation coating. The amount of precious metal used is less than that of coating baking method and water electrolysis method, and it is 5-10 times better than other preparation methods calculated by the attached amount, and the cost is greatly reduced, and it has excellent catalytic performance. At the same time, the vacuum environment in the preparation process prevents the oxidation of the metal substrate in the atmospheric environment that may occur, resulting in an increase in body resistance, and the conductive performance is more excellent. These methods reduce the amount of precious metals to a certain extent, but the coating preparation process is relatively complicated and needs to be further improved. Summary of the invention

[0006] The purpose of the present invention is to overcome at least one of the shortcomings of the prior art and provide a method for constructing a dual-anode layer low-contact impedance PEM water electrolysis membrane electrode. The present invention can avoid direct contact between the anode layer IrOx and the TiO2 on the surface of the gas diffusion layer under the condition of using a titanium felt anode gas diffusion layer without precious metal coating, greatly reduce the contact impedance, and improve the performance of the membrane electrode. At the same time, compared with the use of titanium felt with precious metal coating, the present invention can effectively reduce the amount of precious metals used and the cost of the process.

[0007] The technical solution adopted by the present invention is: A method for constructing a double-anode layer low-contact impedance PEM water electrolysis membrane electrode comprises the following steps: preparing a first anode ink, wherein the first anode ink is composed of a mixture of an ionomer, deionized water, a catalyst and an alcohol solvent; Prepare a second anode ink, wherein the second anode ink comprises an ionomer, deionized water, and a conductivity of not less than 10 5 S / m catalyst and alcohol solvent mixture; Spraying a first anode ink on one side of a proton exchange membrane to form an anode coating A; A second anode ink is further sprayed on the anode coating A to form an anode coating B. In the anode coating B, the catalyst loading is 0.1-1.0 mg / cm 2 , forming an anode catalyst layer with a double-layer structure; forming a cathode catalyst layer on the other side of the proton exchange membrane; Uncoated titanium material is used as the anode gas diffusion layer, and the anode gas diffusion layer, the cathode gas diffusion layer and the corresponding catalyst layer are aligned and compressed to assemble into a membrane electrode to obtain a PEM water electrolysis membrane electrode.

[0008] In some examples of the construction method, the content of the ionomer in the first anode ink is 5-20 wt %.

[0009] In some examples of the construction method, the catalyst loading in the anode coating A is 0.1-3.0 mg / cm 2 .

[0010] In some examples of the construction method, the catalyst in the first anode ink is selected from at least one of an Ir-based catalyst, a Ru-based catalyst, an IrRu alloy catalyst, and a supported catalyst thereof.

[0011] In some examples of the construction method, the content of the ionomer in the second anode ink is 5-20 wt %.

[0012] In some examples of the construction method, the loading amount of the noble metal catalyst in the anode coating B is 0.1-0.3 mg / cm 2 .

[0013] In some examples of the construction method, the catalyst in the second anode ink is at least one of Pt, Pt alloy, Ir, Ru and supported catalysts thereof.

[0014] In some examples of the construction method, the anode gas diffusion layer is made of titanium felt, titanium mesh or sintered titanium plate.

[0015] In some examples of the construction method, the cathode gas diffusion layer is made of carbon paper, titanium felt, titanium mesh or sintered titanium plate.

[0016] In some examples of the construction method, the alcohol solvent in the first anode ink and the second anode ink is selected from at least one of n-propanol, isopropanol and ethanol.

[0017] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0018] The beneficial effects of the present invention are: The construction method of some embodiments of the present invention can directly use low-cost titanium materials such as titanium felt without precious metal coating as the anode gas diffusion layer and realize a low contact impedance interface between the anode layer and the anode layer. At the same time, the catalyst loading in the anode is controlled at 0.3 mg Pt / cm 2 Excellent performance can be achieved with a loading of 1.0 mg Pt / cm 2 Compared with the PEM water electrolysis membrane electrode using titanium felt as the anode gas diffusion layer, the performance of the PEM water electrolysis membrane electrode prepared by this method is close to or even better; it can significantly reduce the use of precious metals, the process is simpler, and the cost of the membrane electrode is effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a comparison of polarization curves of the PEM water electrolysis membrane electrode test in Comparative Example 1, Comparative Example 2 and Example 3.

[0020] Figure 2 This is a comparison of the AC impedance spectra of the PEM water electrolysis membrane electrodes in comparative example 1, comparative example 2 and embodiment 3.

[0021] Figure 3 It is a comparison of polarization curves of the PEM water electrolysis membrane electrode test in Examples 1 to 3. DETAILED DESCRIPTION

[0022] A method for constructing a double-anode layer low-contact impedance PEM water electrolysis membrane electrode comprises the following steps: preparing a first anode ink, wherein the first anode ink is composed of a mixture of an ionomer, deionized water, a catalyst and an alcohol solvent; Prepare a second anode ink, wherein the second anode ink comprises an ionomer, deionized water, and a conductivity of not less than 10 5 S / m catalyst and alcohol solvent mixture; Spraying a first anode ink on one side of a proton exchange membrane to form an anode coating A; A second anode ink is further sprayed on the anode coating A to form an anode coating B. In the anode coating B, the catalyst loading is 0.1-1.0 mg / cm 2 , forming an anode catalyst layer with a double-layer structure; forming a cathode catalyst layer on the other side of the proton exchange membrane; Uncoated titanium material is used as the anode gas diffusion layer, and the anode gas diffusion layer, the cathode gas diffusion layer and the corresponding catalyst layer are aligned and compressed to assemble into a membrane electrode to obtain a PEM water electrolysis membrane electrode.

[0023] The electrical conductivity of the present invention refers to the electrical conductivity at the working temperature of the PEM water electrolysis membrane electrode, specifically, the electrical conductivity at 0 to 100°C.

[0024] The coating can be achieved using various common coating methods, including but not limited to spraying, knife coating, transfer printing and slot coating.

[0025] In some examples of the construction method, the content of the ionomer in the first anode ink is 5-20 wt %. The ionomer can separate the catalyst particles well, prevent the particles from agglomerating, and help to form a film.

[0026] In some examples of the construction method, the catalyst loading in the anode coating A is 0.1-3.0 mg / cm 2 The catalyst loading can be adjusted according to specific needs to meet the needs of water electrolysis. Under the condition of meeting the use requirements, the lower the catalyst loading, the more conducive it is to reducing the cost of PEM water electrolysis membrane electrode.

[0027] There are no special requirements for the catalyst in the first anode ink, and it can be selected from catalysts commonly used in the art. In some examples of the construction method, the catalyst in the first anode ink is selected from at least one of an Ir-based catalyst, a Ru-based catalyst, an IrRu alloy catalyst, and a supported catalyst thereof. The Ir-based catalyst is preferably IrOx, because IrOx has better stability, durability and catalytic performance, and has a lower overall use cost, and is a better choice.

[0028] In some examples of the construction method, the content of the ionomer in the second anode ink is 5-20 wt %. The ionomer can separate the catalyst particles well, prevent the particles from agglomerating, and help to form a film.

[0029] In some examples of the construction method, the catalyst loading in the anode coating B is 0.1-0.3 mg / cm 2 The catalyst loading can be adjusted according to specific needs to meet the needs of water electrolysis. Experimental data show that when the catalyst loading is 0.3 mg Pt / cm 2 When the PEM electrolysis membrane electrode is prepared, the performance is better than that of the electrode with a loading of 1.0 mg Pt / cm 2 The PEM water electrolysis membrane electrode prepared by the plated titanium felt can significantly reduce the amount of catalysts such as Pt without reducing the performance of the PEM water electrolysis membrane electrode, thereby significantly reducing the cost of the PEM water electrolysis membrane electrode.

[0030] The catalyst in the second anode ink has an acceptable tolerance and a 5 In some examples of the construction method, the catalyst in the second anode ink is at least one of Pt, Pt alloy, Ir, Ru and supported catalysts thereof, and may also be oxides thereof. Considering the stability and cost of the material, Pt is preferred.

[0031] In some examples of the construction method, the anode gas diffusion layer is made of titanium felt, titanium mesh or sintered titanium plate. Titanium felt has a lower overall cost and is a better choice.

[0032] In some examples of the construction method, the cathode gas diffusion layer is made of carbon paper, titanium felt, titanium mesh or sintered titanium plate. Carbon paper has a lower overall cost and is a better choice.

[0033] The alcohol solvent can wet and disperse the catalyst. In some examples of the construction method, the alcohol solvent in the first anode ink and the second anode ink is selected from at least one of n-propanol, isopropanol and ethanol.

[0034] The above features can be combined arbitrarily as long as they do not conflict with each other.

[0035] The technical solution of the present invention is further illustrated below in conjunction with examples.

[0036] Preparation of different inks: Weigh 3 g of ionomer, 9.5 g of deionized water and 7 g of n-propanol and mix them evenly. Slowly add 5 g of IrOx catalyst to the mixed dispersion. Ultrasonic disperse the catalyst ink obtained after the catalyst is completely added and wetted for 40 minutes. Finally, dilute the ultrasonically dispersed catalyst ink with 30 wt % of n-propanol to a solid content of 15 wt % to obtain anode ink 1.

[0037] Weigh 0.6 g of ionomer, 3.3 g of deionized water and 2.1 g of n-propanol and mix them evenly. Slowly add 1 g of Pt black catalyst to the mixed dispersion. Ultrasonic disperse the catalyst ink obtained after the catalyst is completely added and wetted for 40 minutes. Finally, dilute the ultrasonically dispersed catalyst ink with 30 wt % n-propanol to a solid content of 15 wt % to obtain anode ink 2.

[0038] Weigh 2.4 g of ionomer, 16.8 g of deionized water and 3.6 g of n-propanol and mix them evenly. Slowly add 1.7 g of Pt / C catalyst to the mixed dispersion. Ultrasonic disperse the catalyst ink obtained after the catalyst is completely added and wetted for 40 minutes. Finally, dilute the ultrasonically dispersed catalyst ink with 15 wt % n-propanol to a solid content of 7.5 wt % to obtain cathode ink.

[0039] Example 1 Preparation of membrane electrode Anode catalyst layer: spray anode ink 1 onto a 6×6 cm 2 The Ir loading on the proton exchange membrane is 1 mg / cm 2 , which is the anode coating A. Then the anode ink 2 is sprayed onto the anode coating A area, and the Pt loading is 0.1 mg / cm 2 , which is the anode coating B. The anode coatings A and B together constitute the anode coating of this example.

[0040] Cathode catalyst layer: Spray cathode ink onto the other side of the proton exchange membrane with a Pt loading of 0.5 mg / cm 2 , which coating constitutes the cathode coating.

[0041] Membrane electrode assembly: The anode gas diffusion layer is titanium felt, and the cathode gas diffusion layer is carbon paper. The gas diffusion layer and the corresponding catalyst layer are aligned and compressed to form a membrane electrode.

[0042] Example 2 Preparation of membrane electrode Anode catalyst layer: spray anode ink 1 onto a 6×6 cm 2 The Ir loading on the proton exchange membrane is 1 mg / cm 2 , which is the anode coating A. Then the anode ink 2 is sprayed onto the anode coating A area, and the Pt loading is 0.2 mg / cm 2 , which is the anodic coating B. The anodic coatings A and B together constitute the anodic coating of this example.

[0043] Cathode catalyst layer: Spray the cathode ink onto the other side of the proton exchange membrane with a Pt loading of 0.5 mg / cm 2 , which coating constitutes the cathode coating.

[0044] Membrane electrode assembly: The anode gas diffusion layer is titanium felt, and the cathode gas diffusion layer is carbon paper. The gas diffusion layer and the corresponding catalyst layer are aligned and compressed to form a membrane electrode.

[0045] Example 3 Preparation of membrane electrode Anode catalyst layer: spray anode ink 1 onto a 6×6 cm 2 The Ir loading on the proton exchange membrane is 1 mg / cm 2 , which is the anode coating A. Then the anode ink 2 is sprayed onto the anode coating A area, and the Pt loading is 0.3 mg / cm 2 , which is the anodic coating B. The anodic coatings A and B together constitute the anodic coating of this example.

[0046] Cathode catalyst layer: Spray the cathode ink onto the other side of the proton exchange membrane with a Pt loading of 0.5 mg / cm 2 , which coating constitutes the cathode coating.

[0047] Membrane electrode assembly: The anode gas diffusion layer is titanium felt, and the cathode gas diffusion layer is carbon paper. The gas diffusion layer and the corresponding catalyst layer are aligned and compressed to form a membrane electrode.

[0048] Comparative Example 1 Preparation of membrane electrode Anode catalyst layer: spray anode ink 1 onto a 6×6 cm 2 The Ir loading on the proton exchange membrane is 1 mg / cm 2 , which coating constitutes the anodic coating.

[0049] Cathode catalyst layer: Spray the cathode ink onto the other side of the proton exchange membrane with a Pt loading of 0.5 mg / cm 2 , which coating constitutes the cathode coating.

[0050] Membrane electrode assembly: The anode gas diffusion layer is titanium felt, and the cathode gas diffusion layer is carbon paper. The gas diffusion layer and the corresponding catalyst layer are aligned and compressed to form a membrane electrode.

[0051] Comparative Example 2 Preparation of membrane electrode Anode catalyst layer: spray anode ink 1 onto a 6×6 cm 2 The Ir loading on the proton exchange membrane is 1 mg / cm 2 , which coating constitutes the anodic coating.

[0052] Cathode catalyst layer: Spray the cathode ink onto the other side of the proton exchange membrane with a Pt loading of 0.5 mg / cm 2 , which coating constitutes the cathode coating.

[0053] Membrane electrode assembly: The anode gas diffusion layer is a Pt-plated layer (Pt loading is about 1 mg / cm 2) titanium felt, and the cathode gas diffusion layer is carbon paper. The gas diffusion layer and the corresponding catalyst layer are aligned and compressed to form a membrane electrode.

[0054] Performance test of membrane electrode The membrane electrode was placed in a fixture for testing at a temperature of 80°C and an atmospheric pressure. The performance of the sample was evaluated by polarization curve and AC impedance spectrum tests. Figure 1 to Figure 3 shown.

[0055] like Figure 1 As shown, Comparative Example 1 is at 1A / cm 2 and 2A / cm 2 The voltage reached 1.676 V and 1.836 V at the current density value of 1A / cm. In Comparative Example 2, titanium felt with Pt coating was used on the basis of Comparative Example 1. 2 and 2A / cm 2 The voltage reaches 1.65 V and 1.782 V at the current density value of 1.65 V and 1.782 V. Therefore, the use of an anode gas diffusion layer with a precious metal coating can reduce the voltage loss.

[0056] In Example 3, a double coating structure (coating A + coating B) was used, at 1A / cm 2 and 2A / cm 2 The voltage reaches 1.624 V and 1.751 V at the current density value of . It can be seen that the membrane electrode of Example 3 has less voltage loss and a certain improvement in hydrogen production efficiency compared with Comparative Example 2 when using less Pt, which has an unexpected effect.

[0057] like Figure 2 As shown, the ohmic impedance of Example 3 and Comparative Example 2 is significantly lower than that of Comparative Example 1. This further illustrates that the anode layer and the gas diffusion layer of Example 3 and Comparative Example 2 have lower contact impedance, thereby effectively reducing voltage loss.

[0058] Depend on Figure 3 It can be seen that the Pt loading in the anode coating B has a certain influence on the performance of the membrane electrode. In Examples 1 to 3, Example 3 (i.e., the loading is 0.3 mg Pt / cm 2 ) performs best.

[0059] In summary, there is a large contact barrier for electron conduction between IrOx and TiO2 on the surface of titanium felt, which will lead to a large contact impedance at their interface. On the basis of the anode coating A containing IrOx, a coating B containing a high conductive material such as Pt black is further added to form a double anode layer structure. The high conductive material can help the conduction of electrons at the interface, effectively reducing the contact impedance between the titanium anode gas diffusion layer without precious metal coating and the anode catalyst layer.

[0060] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A method for constructing a double anode layer low contact impedance PEM water electrolysis membrane electrode, comprising the following steps: preparing a first anode ink, wherein the first anode ink is composed of a mixture of an ionomer, deionized water, a catalyst and an alcohol solvent; Prepare a second anode ink, wherein the second anode ink comprises an ionomer, deionized water, and a conductivity of not less than 10 5 S / m catalyst and alcohol solvent mixture; Spraying a first anode ink on one side of a proton exchange membrane to form an anode coating A; A second anode ink is further sprayed on the anode coating A to form an anode coating B. In the anode coating B, the catalyst loading is 0.1-1.0 mg / cm 2 , forming an anode catalyst layer with a double-layer structure; forming a cathode catalyst layer on the other side of the proton exchange membrane; Uncoated titanium material is used as the anode gas diffusion layer, and the anode gas diffusion layer, the cathode gas diffusion layer and the corresponding catalyst layer are aligned and compressed to assemble into a membrane electrode to obtain a PEM water electrolysis membrane electrode.

2. The construction method according to claim 1, characterized in that: In the first anode ink, the content of the ionomer is 5-20 wt %.

3. The construction method according to claim 1, characterized in that: In the anode coating A, the catalyst loading is 0.1-3.0 mg / cm 2 .

4. The construction method according to any one of claims 1 to 3, characterized in that: The catalyst in the first anode ink is selected from at least one of an Ir-based catalyst, a Ru-based catalyst, an IrRu alloy catalyst and a supported catalyst thereof.

5. The construction method according to claim 1, characterized in that: In the second anode ink, the content of the ionomer is 5-20 wt %.

6. The construction method according to claim 1, characterized in that: In the anode coating B, the catalyst loading is 0.1-0.3 mg / cm 2 .

7. The construction method according to any one of claims 1 to 3, 5 or 6, characterized in that: The catalyst in the second anode ink is at least one of Pt, Pt alloy, Ir, Ru and supported catalysts thereof.

8. The construction method according to any one of claims 1 to 3, 5 or 6, characterized in that: The anode gas diffusion layer is made of titanium felt, sintered titanium plate or titanium mesh.

9. The construction method according to any one of claims 1 to 3, 5 or 6, characterized in that: The cathode gas diffusion layer is made of carbon paper, titanium felt, sintered titanium plate or titanium mesh.

10. The construction method according to any one of claims 1 to 3, 5 or 6, characterized in that: The alcohol solvent in the first anode ink and the second anode ink is selected from at least one of n-propanol, isopropanol and ethanol.

Citation Information

Patent Citations

  • Construction method of efficient and stable PEM electrolyzed water anode catalyst layer

    CN114808000A

  • Anode gas diffusion layer and preparation method and application thereof

    CN115216798A

  • Preparation method of anode catalyst layer of low-interface-impedance PEM water electrolysis membrane electrode

    CN116905002A

  • Gas diffusion layer with pore structure, surface modification method and application

    CN117051424A

  • Titanium fibrofelt composite material and preparation method and application thereof

    CN118756205A